Efficacy and safety of pemafibrate in patients with chronic kidney disease: A retrospective study. Issue 7 (17th February 2023) - Iwasaki, Masako; Suzuki, Hitoshi; Umezawa, Yukako; Koshida, Takeo; Saito, Midori; Fukuda, Hiromitsu; Takahara, Hisatsugu; Matsuzaki, Keiichi; Suzuki, Yusuke
Abstract : Hypertriglyceridemia and chronic kidney disease (CKD) are known risk factors for cardiovascular disease. However, treatment with statins, which control low-density lipoprotein cholesterol levels, increases the risk of estimated glomerular filtration rate (eGFR) reduction. Although conventional fibrates, such as bezafibrate (Beza-F) and fenofibrate (Feno-F), are the mainstay for hypertriglyceridemia treatment, they may be associated with a risk of increased serum creatinine level and renal dysfunction. Pemafibrate (Pema) is pharmacologically defined as a selective peroxisomal proliferator-activated receptor α modulator which is excreted in bile and not likely to cause renal dysfunction. We evaluated the efficacy and safety of switching from Beza-F or Feno-F to Pema in CKD patients with hypertriglyceridemia. We recruited 47 CKD patients with hypertriglyceridemia who were receiving Beza-F, Feno-F, or eicosapentaenoic acid (EPA) but were switched to Pema from 2018 to 2021. A retrospective analysis of renal function and lipid profiles was performed before and 24 weeks after switching. CKD patients switching from EPA to Pema were used as study control. The effect of Pema on hypertriglyceridemia was equivalent to that of Beza-F or Feno-F. However, after switching to Pema, eGFR showed a marked average improvement of 10.2 mL/min/1.73 m 2 ( P < .001). Improvement in eGFR and levels of n -acetyl-β-d -glucosaminidase and β-2-microglobulin was observed only in cases of switching from Beza-F or Feno-F but not from EPA. Although Beza-F and Feno-F are useful medications for the treatment of hypertriglyceridemia, these are associated with a high risk of renal dysfunction. We also found that the deterioration in eGFR due to Beza-F or Feno-F is reversible with drug withdrawal and may not increase the risk for long-term renal dysfunction. We suggest that Pema may be an effective and safe treatment for hypertriglyceridemia in CKD patients.